Hubungan Ketersediaan Fosfor dan Kelarutan Fe pada Tanah Sawah Sulfat Masam - Muhammad Khalqi Alwi; Fakhrur Razie; Ahmad Kurnain (Acta Solum, 2023)
One of the prospective places for agricultural usage in acid sulfate rice fields, which are typically spread out in lowland areas along coastlines that occasionally undergo flooding. If handled effectively in accordance with the issues found in the land, this site can be developed as a productive agricultural region. Agricultural development on acid sulfate soils frequently encounters a number of issues, including (pH) acidic soil, high iron content, a lack of phosphate availability, and the presence of pyrite (FeS2). In this study, the relationship between P availability, Fe solubility, the Fe-P fraction, pH, Eh, and pyrite depth in acid sulfate paddy fields will be examined. Purposive sampling was used in field research utilizing the survey method in the acid sulphate rice fields of Barito Kuala Regency. This research was based on the distribution map of Fe solubility in Barito Kuala Regency. The results of this study indicate that there are three variables that have a significant effect on P availability: soluble Fe amd Fe-P fraction with the power regression form and a very strong relationship; and soil pH with a linear regression form and a strong relationship. Pyrite depth and soil Eh had no significant relationship with P availability in acid-sulfate lowland rice fields.